Impact of loans to farmers on rice production in funtua local government area katsina state, north west Nigeria - Lawal Ruma, Yazid; Bernard, Amedu; Lawal Rumah, Aisha (SPC Journal of Education, 2020)
This research examined the impact of loans to farmers on rice production in Funtua Local Government Area, Katsina State. Three hy-pothesis; there is no significant difference in the loans lend to farmers for their rice production; there is no significant difference on those farmers that collect loans for rice production and those that did not; there is no significance difference, that loans lend to farmers can affect their production, were tested. The quasi experimental-control group design involving pre and post-tests were used. The target population for this study was thirty thousand, two hundred and thirty one (30,231) farmers within the study Area. The sample of the study consists of one hundred and fifty (150) farmers randomly drawn from five (5) selected towns/villages within the study Area. The data was divided into experimental and control groups. Questionnaire was used in gathering data, the respondents will chose the right opinion running from strongly agreed, agreed, uncertain, disagreed and strongly disagreed based on their experience or perception. Percentage score, Mean and standard deviation of differences between the mean impact of loan to farmers on rice production of experimental and control group and gender were used to answer research questions. The null hypothesis were tested with the aid of SPSS Package using ANOVA and t-test at p =0.05 level of significance. The result obtained shows that: there is no significant difference between farmers that collect loan and those that did not within the mean of 2.4533 and 1.8800 respectively.